PROMOSI ONLINE PADA INDIE CLOTHING INSPIRED27 MALANG - Faris Tri Hidayat; Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2014)
Internet in Indonesia currently is growing rapidly and become the primary needs for its users, the development of social media has also become one of the important factors in the amount of internet users in this country.The aim of this research is to know the application and explaination of online promotion through observation and empiric study in Inspired27. The approach used in this research is Theory of Internet base promotion mix. Qualitative descriptive method is used as the means of analysis in order to get systematical picture of the fact which is actual, accurate regarding the object of analysis. The result shows that Inspired27 has applied online promotion to help the sales. Inspired27 use various online promotions such as website and social media. But they have no research team and division that specifically handle online promotion thus the implication is less maximum.